The Debt’s Time: Inner Charter and Common Law in the Joaquín Costa’s Philosophy of Law - José Manuel Vázquez Romero (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
It is a study about Joaquin Costa’s Philosophy of Law, in the tradition of K. Chr. Fr. Krause and Francisco Giner de los Ríos which analyses the concept legal relationship, in order to clarify the peculiar juridification of the self, the social function of the common law and, finally, its engage with the dictatorship (tutelary).